P32 Does Disease Severity Affect Patient Activation Scores in COPD?. (19th November 2012) - Roberts, NJ; Patel, IS; Kidd, L; Lawrence, M; Booth, J
Abstract : Background: As part of the NHS Plan patients are encouraged to manage their own health. Healthcare professionals have a responsibility to ensure that patients have the right tools and education to self-manage their conditions. Hibbard et al have developed a patient activation measure (PAM) which measures the extent to which individuals have the attributes and skills to manage their condition. The PAM determines how "activated" an individual is and can highlight what help an individual needs to improve self-management skills. For example, Level 2 indicates when patients lack confidence/knowledge to take action, whereas Level 3 is where individuals start to take action. Methods: 18 patients attending consultations or pulmonary rehabilitation(PR) during a one-week period in June 2012 were recruited to participate in this observational study. Results: We recruited 18 COPD patients [8 Females, 10Males, Mean age 68 yrs ±8], eleven with moderate COPD, 5 had severe COPD and 2 had very severe COPD. The group had a mean percent predicted FEV1 of 53% and a mean MRC Score of 3±0.8. Five were current smokers and 12 were ex-smokers. In total there had been 10 respiratory admissions and 45 exacerbations in the last 12 months. The group mean PAM score was 66.9±21, and the mean level of activation was 2.89±1.13. Those who had more hospitalisations in the last 12 months had a lower PAM score (Pearsons correlation= –0.456, p=0.066). There was no correlation between COPD stratification and PAM Score (Pearsons correlation= –0.343, p=0.164). Sub-analysis (Table 1 ) showed 6 patients who had not received PR [mean age 66±5.6, mean MRC Score 2.62±0.48], 8 who were currently doing PR [mean age 71±11, mean MRC Score 3±0.75] and 4 who were post-PR [mean age 67.3±3.6, mean MRC Score 3.38±1.10]. Conclusions: Pilot results show that there was no correlation between COPD severity and PAM Scores. Differences in PAM scores were found between those in current PR, as well as those with more hospitalisations. Further work is needed to evaluate the PAM as a tool for multiple points in an individual's journey such as at diagnosis, after a first or repeat admission and as part of PR programmes.